Architecture design of nitrogen-doped 3D bubble-like porous graphene for high performance sodium ion batteries. Issue 12 (26th October 2017) - Qiao, Yun; Cheng, Xiaoguang; Liu, Yang; Han, Ruimin; Ma, Mengyue; Li, Qingling; Dong, Hongyu; Li, Xiangnan; Yang, Shuting
Abstract : The nitrogen-doped 3D bubble-like porous graphene (N-3DPG) is a promising candidate for apllication in sodium ion batteries for large-scale electrochemical energy storage. Abstract : N-Doped 3D bubble-like porous graphene was synthesized via a simple template directed method using polystyrene nanospheres as a template and low-cost industrial melamine as the nitrogen source. The as-synthesized N-3DPG X possessed a high specific surface area, uniform and controllable porous structure and high nitrogen doping content. Benefiting from these features, the as-obtained N-3DPG4 as an anode for sodium ion batteries delivered a high specific capacity of 310 mA h g −1 after 500 cycles at a current density of 0.2 A g −1, and also excellent rate capability as high as 169 mA h g −1 at 10 A g −1 . This simple synthetic method, unique porous structure and outstanding electrochemical performance demonstrated that N-3DPG is a promising candidate for application in sodium ion batteries for large-scale electrochemical energy storage.